Implementing physically active learning: Future directions for research, policy, and practice - Daly-Smith, Andy (J Sport Health Sci, 2020)
PURPOSE: To identify co-produced multi-stakeholder perspectives important for successful widespread physically active learning (PAL) adoption and implementation. METHODS: A total of 35 stakeholders (policymakers n = 9; commercial education sector, n = 8; teachers, n = 3; researchers, n = 15) attended a design thinking PAL workshop. Participants formed 5 multi-disciplinary groups with at least 1 representative from each stakeholder group. Each group, facilitated by a researcher, undertook 2 tasks: (1) using Post-it Notes, the following question was answered: within the school day, what are the opportunities for learning combined with movement? and (2) structured as a washing-line task, the following question was answered: how can we establish PAL as the norm? All discussions were audio-recorded and transcribed. Inductive analyses were conducted by 4 authors. After the analyses were complete, the main themes and subthemes were assigned to 4 predetermined categories: (1) PAL design and implementation, (2) priorities for practice, (3) priorities for policy, and (4) priorities for research. RESULTS: The following were the main themes for PAL implementation: opportunities for PAL within the school day, delivery environments, learning approaches, and the intensity of PAL. The main themes for the priorities for practice included teacher confidence and competence, resources to support delivery, and community of practice. The main themes for the policy for priorities included self-governance, the Office for Standards in Education, Children's Services, and Skill, policy investment in initial teacher training, and curriculum reform. The main themes for the research priorities included establishing a strong evidence base, school-based PAL implementation, and a whole-systems approach. CONCLUSION: The present study is the first to identify PAL implementation factors using a combined multi-stakeholder perspective. To achieve wider PAL adoption and implementation, future interventions should be evidence based and address implementation factors at the classroom level (e.g., approaches and delivery environments), school level (e.g., communities of practice), and policy level (e.g., initial teacher training).